Air Cucian Beras sebagai ZPT Hidroponik - Lussana Rossita Dewi; Lina Wahyu Juniarti; Praptining Rahayu (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to examine the possibility of rice laundry water as a source of ZPT and additional nutrients in hydroponic systems. The method used in this study is a narrative review with a focus on scientific articles published between 2015-2025 that discuss the potential of rice washing water to increase plant growth hydroponically. Rice washing water has the potential as a source of natural growth regulators and nutritional additives in hydroponic cultivation. The nutrient content in rice washing water will increase when its use is combined with other nutrients and processed by fermentation. Increasing nutrients in rice washing water will provide optimal results for hydroponic plant growth.